(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article considers the modern features of the influence of the processes of shadowization of economic activity on the economic security of enterprises in the context of challenges and threats to economic development. Emphasis is placed on a set of measures that counteract the shadowization of economic activity